Analisis Tingkat Kepatuhan Pasien Dalam Melakukan Perawatan Berulang di Salah Satu Praktek Bersama Dokter Gigi di Sumedang - Aldirafi Gani; Amiruddin Setiawan; Nenny Hendajany; Rahadian Malik; Dedy Agus Purwanto; Taufiq Supriadi (Jurnal Riset Multidisiplin Edukasi, 2026)
This study aims to analyze the relationship between the level of knowledge of oral and dental health and patient compliance in undergoing repeated treatment at one of the Joint Dental Practices in Sumedang. The research method used a quantitative approach with a cross-sectional design. The research sample consisted of 30 respondents randomly selected from patients undergoing repeated treatment. Data collection was carried out through an online questionnaire that had been tested for validity and reliability, consisting of knowledge and compliance instruments. Data analysis used the chi-square test. The results showed a statistically significant relationship between knowledge of oral and dental health and patient compliance (p=0.031). A total of 46.67% of respondents were compliant, 40% were fairly compliant, and 13.33% were non-compliant. The majority of respondents had good knowledge (40%) and were dominated by women (70%), aged 18-30 years (56.67%), and had higher education (73.33%). The conclusion of this study is that good knowledge of oral and dental health plays an important role in increasing patient compliance with repeated treatment. Research recommendations include strengthening patient education and effective communication approaches by dental health workers.